2017
DOI: 10.1017/aer.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of self-deploying high-lift effectors applied to membrane wings

Abstract: Flow separation followed by aerodynamic stall limits the operation of aircraft. Expanding the flight envelope of aircraft has been a goal of aerodynamicists for decades. This work presents findings from tests in the Oregon State University wind tunnel investigating the effectiveness of a passively actuated suction-surface flap on membrane wings. Experiments were conducted on a rigid plate and membrane wings with and without a pop-up flap. All wings had an aspect ratio of 2, while membrane pre-strain and Reynol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Schlüter also showed that the flaps bring the additional benefit of gradual stall rather than a more severe lift crisis. Osterberg and Albertani (2017) carried out a similar study on a flat plate subjected to high angles of attack, coming to the same conclusion. Brücker and Weidner (2014) used flexible flaplets attached on the suction side of a NACA 0020 aerofoil that was subjected to a ramp-up motion.…”
mentioning
confidence: 68%
“…Schlüter also showed that the flaps bring the additional benefit of gradual stall rather than a more severe lift crisis. Osterberg and Albertani (2017) carried out a similar study on a flat plate subjected to high angles of attack, coming to the same conclusion. Brücker and Weidner (2014) used flexible flaplets attached on the suction side of a NACA 0020 aerofoil that was subjected to a ramp-up motion.…”
mentioning
confidence: 68%